DIGITAL TRANSFORMATION IN ISLAMIC EDUCATION: CURRICULUM MERDEKA-BASED LEARNING STRATEGIES TO ENHANCE STUDENT AUTONOMY AND INNOVATION - Azizah , Nur; Sari , Lilis Permita; Setiani , Arin (AL-ADABIYAH: Jurnal Pendidikan Agama Islam, 2025)
This study explores the integration of digital transformation within Islamic education through the lens of the Merdeka Curriculum, emphasizing strategies that foster student autonomy and innovation while preserving Islamic values. Utilizing a qualitative literature review, the research critically analyzes various sources to construct an integrative framework combining pedagogical, technological, ethical, and spiritual dimensions. The findings highlight that successful implementation depends on teacher readiness, school leadership, and reflective learning cultures. A novel contribution of this study is the development of the TPACK+V (Value-sensitivity) model and a value-based technology integration framework, which contextualize digital tools within the moral and spiritual fabric of Islamic education. Case studies illustrate best practices in high-performing schools, while challenges in 3T (frontier, outermost, and disadvantaged) regions underscore the need for differentiated policies. Ultimately, the study offers strategic insights for designing transformative, ethical, and inclusive digital learning in Islamic educational contexts. Penelitian ini mengkaji integrasi transformasi digital dalam pendidikan Islam melalui pendekatan Kurikulum Merdeka, dengan penekanan pada strategi yang mendorong kemandirian dan inovasi peserta didik sekaligus mempertahankan nilai-nilai keislaman. Menggunakan metode tinjauan pustaka kualitatif, studi ini secara kritis menganalisis berbagai sumber untuk membangun kerangka kerja integratif yang mencakup dimensi pedagogis, teknologis, etis, dan spiritual. Temuan menunjukkan bahwa keberhasilan implementasi sangat dipengaruhi oleh kesiapan guru, kepemimpinan sekolah, dan budaya pembelajaran reflektif. Kontribusi baru dari penelitian ini adalah pengembangan model TPACK+V (Value-sensitivity) serta kerangka integrasi teknologi berbasis nilai, yang mengontekstualisasikan penggunaan digital dalam bingkai moral dan spiritual pendidikan Islam. Studi kasus menunjukkan praktik terbaik di sekolah-sekolah unggulan, sementara tantangan di wilayah 3T (terdepan, terluar, tertinggal) menegaskan perlunya kebijakan yang bersifat diferensial. Pada akhirnya, penelitian ini menawarkan wawasan strategis untuk merancang pembelajaran digital yang transformatif, etis, dan inklusif dalam konteks pendidikan Islam.